PRESCRIPTION AUDIT FOR EVALUATION OF PRESCRIBING PATTERN OF THE DOCTORS FOR RATIONAL DRUG THERAPY IN A TERTIARY CARE HOSPITAL - Kaur, Balbir; Walia, Rani (Journal of Drug Delivery and Therapeutics, 2013)
Background: Irrational prescribing is a global problem. In order to promote rational drug usage standard policies on use of drugs must be set, and this can be done only after the current prescription practices have been audited.Â Methods: The study was carried out prospectively over a period of six months in the department general medicine of our tertiary care hospital. Results: 288 prescriptions were analyzed. Total no. of drugs in 288 prescriptions were 2559. Therefore average number of drugs/prescription is 8.8. Drugs were prescribed by generic names in 4.16% of cases, drugs on EDL are only 36.92% and fixed dose combinations are 35.87% of total drugs. Dosage forms used were mostly oral 84.40%. Injectables were only 12.07% and topical forms were least 0.58%. Basic information of patient was written in 100% prescriptions. Complete diagnoses were written in 73.26% prescriptions. Only 86.80% prescriptions were legible and only 72.56% prescriptions were complete in terms of dose, route, strength, frequency and dosage forms. Disease pattern seen was variable. Diseases of cardiovascular system were maximum 33.33% followed by diseases of respiratory system 22.91% and diseases of endocrine system 11.45%. The most common drug groups prescribed were multivitamins, minerals & enzymes, cardiovascular drugs, antiulcer drugs and antibiotics. The incidence of polypharmacy was also common. Conclusions: There is immense scope for improvement in prescribing patterns in areas of writing generic names of drugs, essential drugs, writing legible and complete prescriptions. Polypharmacy was evident from our study.Â Keywords: Prescription auditing, Rational pharmacotherapy, Polypharmacy, Essential drug